2015
DOI: 10.1016/j.math.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Interactive cervical motion kinematics: Sensitivity, specificity and clinically significant values for identifying kinematic impairments in patients with chronic neck pain

Abstract: Interactive cervical motion kinematics: sensitivity, specificity and clinically significant values for identifying kinematic impairments in patients with chronic neck pain. AbstractChronic neck pain has been consistently shown to be associated with impaired kinematic control including reduced range, velocity and smoothness of cervical motion, that seem relevant to daily function as in quick neck motion in response to surrounding stimuli. The objectives of this study were: to compare interactive cervical kinema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 37 publications
5
33
0
Order By: Relevance
“…In our case for example, it is known that patients with neck pain have poorer sensory-motor control with open eyes, characterized by an increase in joint positioning error and a decrease in speed and acceleration during all movements [12]. The absence of difference in our kinematics data between patients and participants could seem unexpected as previous studies showed significant differences in terms of kinematics [5,46]. However this absence of difference could be explained by our sample size, resulted in low power, and by the difficulty for the DidRen laser to discriminate between such groups [47,48].…”
Section: Discussionmentioning
confidence: 58%
“…In our case for example, it is known that patients with neck pain have poorer sensory-motor control with open eyes, characterized by an increase in joint positioning error and a decrease in speed and acceleration during all movements [12]. The absence of difference in our kinematics data between patients and participants could seem unexpected as previous studies showed significant differences in terms of kinematics [5,46]. However this absence of difference could be explained by our sample size, resulted in low power, and by the difficulty for the DidRen laser to discriminate between such groups [47,48].…”
Section: Discussionmentioning
confidence: 58%
“…Recently, accuracy in following a moving target in a virtual environment has been shown to be somewhat sensitive and specific to those with neck pain. 4 To date, no specific differences in those with traumatic neck pain compared to INP have been noted, but this is a continued area of investigation (FIGURE 3).…”
Section: Cervical Proprioceptionmentioning
confidence: 99%
“…Neck pain (NP) is a global problem [1], with a reported lifetime prevalence of about 70% in different populations [2,3]. Patients with NP have demonstrated impairment in a wide range of sensorimotor functions [4-7]. The density of mechanoreceptors and muscle spindles in cervical region has increased [8,9], and these elements are associated with vestibular, visual and postural control systems which provide information that is important in regulating postural balance [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite potential benefits of VR technology in physical rehabilitation [19] and pain reduction [20-24], only a few studies have evaluated the efficacy of this type of treatment in patients with NP [26,27]. Recently, a VR device was developed to assess [7] and treat [26] cervical kinematics in patients with NP. In a pilot study to compare the effects of cervical kinematic training with and without this new VR device, between-group analysis showed improvements in overall perceived change in VR plus kinematic training group but no significant improvement in neck disability, range of motion or dynamic balance [26].…”
Section: Introductionmentioning
confidence: 99%